FACTORS RELATED TO SELF-CARE ACTIVITIES IN THE ELDERLY WITH DIABETES MELLITUS IN BENER MERIAH REGENCY - Fati, Lina; Asniar, Asniar; Susanti, Suryane Sulistiana (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
The number of Diabetes Mellitus (DM) survivor were continuously increasing, especially among the elder population. This study aims to identify any factors associated with self-care activities in the elder with DM, also the relationship between knowledge, self-efficacy, and family support to the self-care activities in such population. The data were collected using a questionnaire and analyzed using SPSS for univariate, bivariate (Pearson), and multivariate (logistic regression) techniques. The results indicate that there was a relationship between knowledge and self-care activities in the elder with DM (0.000 0.05), and there was no relationship between self-efficacy and self-care activities (0.824 0.05). Moreover, a significant relationship showed between knowledge and self-care activities (0.000 0.05), and based on the linear regression test results, this research concluded that family support (0.000 0.05) become the most decisive factor and influence on self-care activities in the elder with diabetes mellitus in Bener Meriah